On the Road Without a Map: Why We Need an “Ethic of Road Ecology” - Moore, Lauren J.; Arietta, A. Z. Andis; Spencer, Daniel T.; Huijser, Marcel P.; Walder, Bethanie L.; Abra, Fernanda D. (Frontiers in Ecology and Evolution, 2021)
Over the past two decades, our knowledge of the ecological impacts of roads has increased rapidly. It is now clear that the environmental effects of transportation infrastructure are inextricable from transportation benefits to economic, social, and cultural values. Despite the necessity of optimizing these multiple values, road planners, scientists and practitioners have no established methodology or pluralistic approach to address growing ethical complexities. We articulate five ethical issues that could be addressed by developing an ethic of road ecology in order to facilitate the identification, reasoning, and harmonization of ethical dimensions of road planning and development. This inquiry into road ecology can draw lessons from existing applied ethics, such as in ecological restoration and urban planning, to build a narrative that is informed by both science and ethics. We illustrate five ethical issues presented through case studies that elaborate on the motivations, responsibilities, and duties that should be considered in ethically and scientifically complicated road building decisions. To address these issues, we encourage the development of a code of ethics, dedicated intellectual forums, and practical guidance to assist road planners, and more broadly transportation practitioners, to resolve complex ethical quandaries systematically. We hope this perspective encourages conversation for a holistic yet pragmatic approach to this applied ethics problem, while also assisting responsible parties as they navigate difficult moral terrain.